La planificación estratégica y la toma de decisiones en la empresa Smart Electronics de la ciudad de Riobamba. - Ayala Pinduisaca, Jorge Luis (2024)
ABSTRACT: In this research work, the importance of strategic planning and decision-making in the company "Smart Electronics" in Riobamba was identified to determine the impact of strategic planning on decision-making. A theoretical framework was developed that will help with information about the two variables to be studied. It was implied that currently, decision-making is part of all daily and business activities and has not been given the necessary importance since Making decisions must take into account several elements such as the time to analyze information, the pressure it entails, the stability of the environment and many other equally important factors. Strategic planning plays a vital role in this variable since it provides a series of techniques and tools that help collect information and control the processes to be followed as planned. Strategic planning is the process of documenting and establishing a direction for the company, evaluating where it is and where it wants to go. In this way, the mission, vision, values, policies, long-term objectives, and action plans that will be carried out to achieve them are established. In the methodological part, the hypothetical-deductive method was chosen, which made it possible to verify or deny the proposed hypotheses, collect and analyze data, and provide results. Descriptive, explanatory, and non-experimental research was used, which allowed the study of the research phenomenon, the solving of the problem posed, and the making of conclusions and recommendations in this research.